Competence model of personality of the graduate of the master's program in the direction 44.04.02 - psychological and pedagogical education - Minyurova Svetlana Aligaryevna; Aminova Jennet Kamilyevna (Política e Gestão Educacional, 2021)
The article is devoted to the actual problem of the formation and development of the personality of a master student studying in the direction 44.04.02 - psychological and pedagogical education. With the introduction of new standards into educational practice, an urgent need arose to build a graduate model, according to competencies. The authors place particular emphasis on the methodological analysis of the foundations for the development of professionalism, on the patterns of formation of the labor functions of the teacher-psychologist. In their search for truth, researchers used only theoretical tools of knowledge, such as the axiomatic method, modeling, analysis, synthesis, idealization. Thanks to which the authors prescribe the content characteristics of the components of the competence model of a graduate of a pedagogical university in the direction of training "Psychological and pedagogical education". This model consists of professional, motivational, value and personal components.